Training on Halal and Eco-friendly Canteen Practises for Micro-Entrepreneurs within the Campus Environment - Hirawati Oemar; Aan Komariah; Yan Orgianus; Ulima Alifani (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The canteen has a crucial role in delivering halal, safe, and healthy food as well as environmental protection. However, many processed food microentrepreneurs lack halal certification for their products and do not effectively manage waste. Registration for halal certification has been challenging due to a lack of education, information, and dedication. Tertiary institutions should provide training on product halal assurance systems, technical registration of halal certification through a self-declaring scheme, and 3R-based waste management (Reduce, Reuse, Recycle) as a form of community service so that they can become eco-friendly halal canteens. This is consistent with the concept of rahmatan lil alamin. Questionnaire distribution is used to test the measurement of training results. Following the training, it was discovered that participants' knowledge of halal products, how to acquire halal certification, and waste management had improved. Canteen microentrepreneurs demonstrate their willingness to apply for halal certification and execute 3R-based waste management.